A scoping review of interventions for older adults transitioning from hospital to home. Issue 10 (19th June 2021) - Liebzeit, Daniel; Rutkowski, Rachel; Arbaje, Alicia I.; Fields, Beth; Werner, Nicole E.
Abstract: Background/Objectives: Older adults are at high risk for adverse outcomes as they transition from hospital to home. Transitional care interventions primarily focus on care coordination and medication management and may miss key components. The objective of this study is to examine the current scope of hospital‐to‐home transitional care interventions that impact health‐related outcomes and to examine other key components including engagement by older adults and their caregivers. Design: Scoping review. Methods: Eligible articles focused on hospital transition to home intervention, measured primary outcomes posthospitalization, used randomized controlled trial designs, and included primarily adults aged 60 years and older. Articles included in this review were reviewed in full and all data were extracted that related to study objective, setting, population, sample, intervention, primary and secondary outcomes, and main results. Results: Five hundred sixty‐seven records were identified by title. Forty‐four articles were deemed eligible and included. Most common transitional care intervention components were care continuity and coordination, medication management, symptom recognition, and self‐management. Few studies reported a focus on caregiver needs or goals. Common modes of intervention delivery included by phone, in person while the patient was hospitalized, and in person in the community following hospital discharge. The most common outcomes were readmission and mortality. Conclusion: To improve outcomes beyond healthcare utilization, a paradigm shift is required in the design and study of care transition interventions. Future interventions should explore methods or novel interventions for caregiver engagement; leverage an interdisciplinary team or care coordination hub with engagement from underrepresented specialties such as social work and occupational therapy; and examine opportunities for interventions designed specifically to address older adult and caregiver‐reported needs and their well‐being.